Utilization of Granular Organic Fertilizer from Sorghum Ethanol Distillation Waste in Leda (Eucalyptus deglupta) Nursery on Andosol, Latosol, and Podzolic PEMANFAATAN PUPUK ORGANIK GRANULAR DARI LIMBAH DESTILASI ETANOL SORGUM UNTUK PEMBIBITAN LEDA .... - Supriyanto .; Ardiyansyah Purnama (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Sorghum (Sorghum bicolor L Moenc) is plant for food, feed, and energy (bio-ethanol). There were two types of waste from bio-ethanol production, such as liquid and solid waste (baggase). Liquid waste was produced from ethanol distillation process, rich in nutrients as fertilizer, unfortunately limited information on nutritional content and potential function, especially as medium for forestry seedlings production. This experiment examined the effect of the Granular Organic Fertilizer of Sorghum liquid waste to Leda seedling growth in different soil type of Andosol, Latosol, and Podzolic; and to find the dose of Granular Organic Fertilizer for Leda seedling growth in each type of soil. This study was conducted on Factorial in Completely Randomized design. The result showed, the application of Granular Organic Fertilizer effected to almost all the growth parameters on three soil types. Best seedling quality index of leda was found in the combination of Andosol and 20 granules of Granular Organic Fertilizer with seedling quality index 30 points.Key words: andosol, granular organic fertilizer, latosol, podzolic, sorghum.